2015
DOI: 10.1128/jcm.01152-15
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of Klebsiella pneumoniae Bloodstream Isolates into Four Distinct Groups byompK36Typing in a Taiwanese University Hospital

Abstract: The OmpK36 porin plays a role in carbapenem resistance and may contribute to bacterial virulence in Klebsiella pneumoniae. This study aimed to investigate the characteristics of different groups of K. pneumoniae separated by ompK36 typing. Among 226 nonduplicate K. pneumoniae bloodstream isolates collected at a Taiwanese hospital in 2011, four ompK36 types, designated types A, B, C, and D, were identified by PCR in 61, 28, 100, and 36 isolates, respectively; 1 isolate was untypeable. Statistical analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…However, these two STs were not found in the present study. Previous studies showed that ST268 was only found among K20 isolates (Liu et al, 2014 ; Lin et al, 2015 ; Yan et al, 2015 , 2016 ; Zhang et al, 2016 ). In the present study, we also found that there was an association between ST268 and K20 isolates.…”
Section: Discussionmentioning
confidence: 94%
“…However, these two STs were not found in the present study. Previous studies showed that ST268 was only found among K20 isolates (Liu et al, 2014 ; Lin et al, 2015 ; Yan et al, 2015 , 2016 ; Zhang et al, 2016 ). In the present study, we also found that there was an association between ST268 and K20 isolates.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, we demonstrated that the sequence type ST76 was the predominant type among CRKP isolates which are bla KPC-2 positive in Heilongjiang Province. To the best of our knowledge, the ST76 clone has been sporadically reported in Taiwan and America [ 45 , 46 ]. In Japan, ST76 has been isolated from meat [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though some major international ST (ST11, ST14, ST147, ST258) strains of MDR K. pneumoniae are called sometimes hypervirulent or "high-risk" an abundance of papers show that these isolates carry significantly fewer virulence factors than strains from the really highly virulent STs, primarily ST23 and ST65 (Lascols et al, 2013;Bialek-Davenet et al, 2014;Liu et al, 2014;Qu et al, 2015;Yan et al, 2015;Paczosa and Mecsas, 2016;Gomez-Simmonds and Uhlemann, 2017;Gu et al, 2018;Lam et al, 2018b;Turton et al, 2018). Interestingly -despite the large outfit of virulence factors -ST23 and ST65 strains remain minor STs relative to the major clones of MDR K. pneumoniae in the healthcare setting (Cantón et al, 2012;Chen et al, 2014;Pitout et al, 2015;Gomez-Simmonds and Uhlemann, 2017;Runcharoen et al, 2017).…”
Section: The Virulence Component In Mdr K Pneumoniaementioning
confidence: 99%